Intrapartum Sonographic Measurement of Amniotic Fluid Volume for Prediction of Poor Fetal Outcomes in Low Risk Pregnancy - Pornsri Niransuk; Somsri Pitukkijronnakorn; Apichart Chittacharoen (The Royal Thai College of Obstetricians and Gynaecologists, 2014)
Objective: To determine the diagnostic value of intrapartum amniotic fluid volume, with single deepest pocket (SDP) technique, for prediction of poor fetal outcomes in low risk pregnancy.Materials and Methods: A cross-sectional study was conducted on 454 low risk singleton term pregnancies who delivered from April 2012-August 2012 at Ramathibodi Hospital. Ultrasonography estimated SDP was performed as an admission test and then continuous intrapartum electronic fetal monitoring (EFM) was done. Oligohydramnios was defined as a SDP ≤ 2.0 cm. The criteria for diagnosis of poor fetal outcomes were Apgar score at 5 minute ≤ 7, meconium stained amniotic fluid, abnormal EFM and neonatal intensive care unit (NICU) admission. Results: A total 454 low risk singleton pregnancies was enrolled. Thirty eight cases (8.4%) were diagnosed as oligohydramnios by SDP technique and 19 cases of these had poor fetal outcomes. The sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV) of SDP ≤ 2.0 cm for prediction of poor fetal outcomes were 20.9%, 94.8%, 82.7%, and 50.0%, respectively. After subgroup analysis, the sensitivity and specificity of oligohydramnios for prediction of meconium stained amniotic fluid was 25.4%, 94.2% and abnormal EFM was 25.0%, 92.9%, respectively. The relative risk of oligohydramnios with meconium stained amniotic fluid and abnormal EFM were 3.7 (95% CI; 2.3, 6.0) and 3.6 (95%CI; 1.7, 7.5), respectively. However, the significance of low Apgar score at 5 minute and NICU admission could not be evaluated due to low incidence. Conclusion: The intrapartum assessment of oligohydramnios by SDP ≤ 2.0 cm had high specificity for prediction of poor fetal outcomes and also was associated with increased risk of meconium stained amniotic fluid and abnormal EFM.